Impact of Different Initial Epinephrine Treatment Time Points on the Early Postresuscitative Hemodynamic Status of Children With Traumatic Out-of-hospital Cardiac Arrest. Issue 12 (March 2016) - Lin, Yan-Ren; Syue, Yuan-Jhen; Buddhakosai, Waradee; Lu, Huai-En; Chang, Chin-Fu; Chang, Chih-Yu; Chen, Cheng Hsu; Chen, Wen-Liang; Li, Chao-Jui
Abstract : Abstract: The postresuscitative hemodynamic status of children with traumatic out-of-hospital cardiac arrest (OHCA) might be impacted by the early administration of epinephrine, but this topic has not been well addressed. The aim of this study was to analyze the early postresuscitative hemodynamics, survival, and neurologic outcome according to different time points of first epinephrine treatment among children with traumatic OHCA. Information on 388 children who presented to the emergency departments of 3 medical centers and who were treated with epinephrine for traumatic OHCA during the study period (2003–2012) was retrospectively collected. The early postresuscitative hemodynamic features (cardiac functions, end-organ perfusion, and consciousness), survival, and neurologic outcome according to different time points of first epinephrine treatment (early: <15, intermediate: 15–30, and late: >30 minutes after collapse) were analyzed. Among 165 children who achieved sustained return of spontaneous circulation, 38 children (9.8%) survived to discharge and 12 children (3.1%) had good neurologic outcomes. Early epinephrine increased the postresuscitative heart rate and blood pressure in the first 30 minutes, but ultimately impaired end-organ perfusion (decreased urine output and initial creatinine clearance) (all P < 0.05). Early epinephrine treatment increased the chance of achieving sustained return of spontaneous circulation, but did not increase the rates of survival and good neurologic outcome. Early epinephrine temporarily increased heart rate and blood pressure in the first 30 minutes of the postresuscitative period, but impaired end-organ perfusion. Most importantly, the rates of survival and good neurologic outcome were not significantly increased by early epinephrine administration.